O uso da fotografia para promoção de saúde mental de trabalhadores da saúde - (:unkn) unknown (Universidade Federal do Amazonas, 2023)
Public health professionals in Brazil are subject to somatic and psychic illness, suffering, and fragility of mental functioning, often due to the conditions of the work environment, which is why the implementation of intervention projects in health units serves as a driving force for the promotion of mental health at work. The use of actions that involve visual arts such as photography presented positive results in the re- signification of suffering, promotion of mental health, strengthening of bonds, and a sense of belonging among workers, but the lack of theoretical data that justifies and consolidates photography as a powerful tool for the elaboration of studies involving the physical and mental comfort of health professionals. In this way, the present study aimed to carry out bibliographical research of a descriptive nature, using the qualitative method of essayistic nature to understand the dynamics of suffering faced by Brazilian public health workers, who learned photography as a tool to promote mental health and quality of life. We analyzed the theoretical potential of photography as a tool for re- significate the suffering and prevention of mental illness at work for health professionals and contextualized health professionals in the context of the public hospital work. A survey and analysis of theoretical data on photography, art therapy and mental health in public health workers was carried out from an organizational perspective, respecting the workers' experiences without ignoring the hierarchical issues and lines of tension existing in the hospital reality in the BVS Psicologia Brasil and in the DeCS /MeSH, as well as Periodicals CAPES/MEC, Periodicals Electronics in Psychology, ScientificElectronic Library Online, Latin American and Caribbean Literature in Sciences and Google Scholar itself, but no results were found that addressed these terms together, evidencing the pioneering nature of this study. A methodology was also proposed that conceives photography as a tool for redefining the suffering of health professionals, linking the author's personal experiences with a technical view of the use of photography during physical and mental stress. Based on the results obtained, we identify an interest in the literature on the benefits of art therapy on body expression on people's emotional and affective characteristics. The present study brought the contribution of using photography to recognize the importance of primary care services and to strengthen how much health is, associated with the promotion of dialogic construction spaces to provide spontaneous motivation in the psyche of hospital workers. It was possible to recognize the power of photography as an instrument for re-significate the sources of suffering and illness in the work of health professionals, stimulating relevant reflections on equality, professional preservation, and healthy coexistence at work.
Keywords: Trabalho - Aspectos psicológicos; Estresse ocupacional; Serviços de saúde ocupacional; CIENCIAS HUMANAS: PSICOLOGIA: PSICOLOGIA DO TRABALHO E ORGANIZACIONAL; Ressignificação; Trabalhadores da saúde; Fotografia; Psicodinâmica do trabalho; Promoção da saúde